Cyst‐motile stage relationship, morphology, ultrastructure, and molecular phylogeny of the gymnodinioid dinoflagellate Barrufeta resplendens comb. nov., formerly known as Gyrodinium resplendens, isolated from the Gulf of Mexico. Issue 5 (13th September 2015) - Gu, Haifeng; Luo, Zhaohe; Mertens, Kenneth Neil; Price, Andrea Michelle; Turner, Robert Eugene; Rabalais, Nancy N.
Abstract : In the present study, we redescribed Gyrodinium resplendens through incubation of process bearing cysts extracted from sediment collected in the northern Gulf of Mexico. The morphology and ultrastructure of the motile stage and cyst stage were examined using light microscopy, scanning electron microscopy, and transmission electron microscopy and this revealed that the species should be transferred to the genus Barrufeta . This genus differs from other gymnodinioid genera in possessing a Smurf‐cap apical structure complex (ASC) and currently encompasses only one species, Barrufeta bravensis . B. resplendens shows a Smurf‐cap ASC that consists of three rows of elongated vesicles with small knobs in the middle one. B. resplendens is very similar to B. bravensis in cell morphology, but can be separated using the ultrastructure such as the shape and location of nucleus and pyrenoids, which highlights the importance of ultrastructure at inter‐specific level in the genus Barrufeta . The unique cysts of B. resplendens are brown and process bearing, and have a tremic archeopyle with a zigzag margin on the dorsal side of the epicyst, and not polar as in cysts of Polykrikos . The cysts do not survive the palynological treatment used here and probably have a wide distribution. Maximum‐likelihood and Bayesian inference were carried out based on partial large subunit ribosomal DNA (LSU rDNA) sequences. Molecular phylogeny supports that the genus Barrufeta is monophyletic, and that the genus Gymnodinium is polyphyletic. Our results suggest that details of the ASC together with ultrastructure are potential features to subdivide the genus Gymnodinium .